2017
DOI: 10.3928/1081597x-20170807-01
|View full text |Cite
|
Sign up to set email alerts
|

Four-Stage Procedure for Keratoconus: ICRS Implantation, Corneal Cross-linking, Toric Phakic Intraocular Lens Implantation, and Topography-Guided Photorefractive Keratectomy

Abstract: This four-stage procedure appears to be an effective and safe approach for corneal stabilization and improvement of functional vision in patients with keratoconus. Larger case series with a longer follow-up are required to thoroughly evaluate the efficacy, safety, and stability of this combined approach. [J Refract Surg. 2017;33(10):683-689.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 24 publications
0
4
0
6
Order By: Relevance
“…As a result, accurate and precise measurement of anterior segment parameters and keratometry readings are of great importance for preoperative planning and follow-up of managing keratoconus. 2 In patients with keratoconus, the primary source of refractive error is considered a steep corneal curvature due to ectasia, but increased axial length can also contribute to myopia according to previous studies. However, when using emmetropic eyes as the control group, these eyes might have tended to be shorter than the general population, resulting in axial elongation being detected in KC patients in most published studies.…”
Section: Introductionmentioning
confidence: 96%
“…As a result, accurate and precise measurement of anterior segment parameters and keratometry readings are of great importance for preoperative planning and follow-up of managing keratoconus. 2 In patients with keratoconus, the primary source of refractive error is considered a steep corneal curvature due to ectasia, but increased axial length can also contribute to myopia according to previous studies. However, when using emmetropic eyes as the control group, these eyes might have tended to be shorter than the general population, resulting in axial elongation being detected in KC patients in most published studies.…”
Section: Introductionmentioning
confidence: 96%
“…Ophthalmologists need to be familiar with the special planning for IOL power calculation in patients with KCN. Recent studies have suggested that new preoperative therapeutic methods including CXL or ICRS implantation may help to provide more predictable and stable outcomes after cataract surgery 10, 52, 53, 54…”
Section: Discussionmentioning
confidence: 99%
“…Όλες στηρίζονται στο συνεργιστικό ρόλο των δυο τεχνικών, της διασύνδεσης του κερατοειδικού κολλαγόνου (CXL) κυρίως για την βιοµηχανική σταθερότητα του κερατοειδούς και την κατά το δυνατόν οµαλοποίηση της ανώµαλης επιφάνειας του κερατοειδούς µε την επιπέδωση του και της ένθεσης του φακικού ενδοφακού (p-IOL), συνήθως µετά από διάστηµα 6-12 µηνών, για την διόρθωση του υψηλού διαθλαστικού σφάλµατος [207][208][209][210]. Ο συνδυασµός των δυο αυτών τεχνικών έχει το πλεονέκτηµα της διόρθωσης ακόµα και υψηλών αµετροπιών αλλά και το µειονέκτηµα ότι δεν µπορεί να διορθωθεί ιδιαίτερα ανώµαλος αστιγµατισµός.Η διασύνδεση του κερατοειδικού κολλαγόνου (CXL) µπορεί επιπλέον να συνδυαστεί και µε περισσότερες της µιας διαθλαστικές τεχνικές [211][212][213][214][215][216]. Έτσι, έχουν αναφερθεί αποτελέσµατα ποικίλων συνδυασµών των διαφόρων τεχνικών [211][212][213][214][215][216].…”
unclassified
“…Ο συνδυασµός των δυο αυτών τεχνικών έχει το πλεονέκτηµα της διόρθωσης ακόµα και υψηλών αµετροπιών αλλά και το µειονέκτηµα ότι δεν µπορεί να διορθωθεί ιδιαίτερα ανώµαλος αστιγµατισµός.Η διασύνδεση του κερατοειδικού κολλαγόνου (CXL) µπορεί επιπλέον να συνδυαστεί και µε περισσότερες της µιας διαθλαστικές τεχνικές [211][212][213][214][215][216]. Έτσι, έχουν αναφερθεί αποτελέσµατα ποικίλων συνδυασµών των διαφόρων τεχνικών [211][212][213][214][215][216]. Κοινή συνισταµένη όλων αυτών των συνδυασµών είναι η σταθεροποίηση της εκτατικής διαταραχής του κερατοειδούς µε την διασύνδεση του κερατοειδικού κολλαγόνου (CXL) και η µέγιστη δυνατή βελτίωση της οπτικής οξύτητας των κερατοκωνικών ασθενών µε το συνδυασµό των αντίστοιχων διαθλαστικών τεχνικών [211][212][213][214][215][216].…”
unclassified
See 1 more Smart Citation